Studi Penggunaan Antibiotik pada Kasus Bedah Apendiks di Instalasi Rawat Inap RSD dr. Soebandi Jember Tahun 2013 (The Use of Antibiotics in Case Studies App - Fandy Zulfikar; Prihwanto Budi S; Wiratmo Wiratmo (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Appendicitis is one of acute abdominal disease where there is inflammation of the appendix vermiformis. A surgical treatment of appendicitis, called appendectomy, then was needed in this case. Appendectomy surgery is categorized as clean contaminated, required the administration of prophylactic antibiotics to prevent pre-operative surgical wound infection and when perforation found at surgery then antibiotic will be extended as therapy. The antibiotics usage has to be rational. This study was conducted to determine the pattern of antibiotic usage, conformance with standard antibiotic therapy and the rational use of antibiotics that includes the proper indications, the right medication, right dose, right patient, drug side effects and drug interactions alert. The method used was total sampling method and retrospective approach. The sample was all patients who use antibiotics for the diagnosis of appendicitis in RSD dr. Soebandi Jember starting from 1 January to 31 December 2013. The results showed that the most widely used type of antibiotic for therapy and prophylaxis was ceftriaxone, 52.87% and 65.28%, suitability between antibiotic used against standardized protocol was 75%, rationality usage of antibiotic was 100%, 100% were right drugs, appropriate dose was 75%, appropriate patients were 99%e, side effects alert were 100%, whereas drug interactions alert were 99%. Keywords: appendicitis, antibiotics, appendectomy